MENELUSURI JEJAK POPULASI MORFOLOGI PANGUR GIGI-GELIGI: KAJIAN PENDAHULUAN ATAS SAMPEL GIGI-GELIGI DARI BEBERAPA SITUS PURBAKALA DI JAWA, BALI, DAN NUSA TENGGARA TIMUR - Toetik Koesbardiyati; Rusyad Adi Suriyanto (Humaniora, 2007)
Filing is a form of dental mutilation which is often practiced as an initiation rite function, that is symbolization that one has already entered and adult culturally; and symbolyzation to remind and to commemorate the family members which have already passed away. Filing was found in almost all ethnic population in Indonesia in the past time; however, nowadays, it is not much done anymore because of several factors. Nevertheless, some ethnic populations still continue this tradition. The patterns of dental filing on those populations relate to the peopling history in the region. The research materials include dentitions of the adult human skulls of Java, Bali and Nusa Tenggara Timur from some paleoanthropological-archaeological sites, as well as isolated permanent dental sample from modern Bali population. The methods used is visual comparative descriptive method. The variation of dental filing patterns include oclusal, labial and lingual grinding, extraction and the sharpening. This patterns relate to the cultural chronology continuity and the peopling of Australomelanesid and Mongolid populations in Indonesia region. This filing patterns may indicate the biological affinity.